beta-glucan ameliorates methotrexate-induced oxidative organ injury via its antioxidant and immunomodulatory effects - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, GÖKSEL (ELSEVIER, 2006)
Methotrexate is an antifolate that is widely used in the treatment of rheumatic disorders and malignant tumors. The efficacy of methotrexate is often limited by severe side effects and toxic sequelae, where oxidative stress is noticeable. In the present study, the possible protective effect of beta-glucan in methotrexate-induced toxicity was investigated. Following a single dose of methotrexate injection (20 mg/kg), either saline or beta-glucan (50 mg/kg; orally) was administered for 5 days. After decapitation of the rats, trunk blood was obtained and the ileum, liver and kidney were removed to measure tissue malondialdehyde (NMA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content, as well as histological examination. Methotrexate caused a significant decrease in GSH levels, while MDA levels, WO activity and collagen content were increased in all the tissues (P < 0.05-0.001). On the other hand, administration of IS-glucan following methotrexate abolished the depletion of GSH and inhibited the increases in MDA, MPO activity and collagen content, while the histological analysis revealed that beta-glucan attenuated the tissue damage. Stimulation index, an indicator of oxidative burst in the neutrophils, was decreased by methotrexate (P < 0.001), while beta-glucan abolished this effect. Furthermore, increased leukocyte apoptosis and cell death in methotrexate-treated animals were inhibited by beta-glucan (P < 0.05). Thus, the findings of the present study suggest that beta-glucan, through its antioxidant and immunoregulatory effects, may be of therapeutic value in alleviating the leukocyte apoptosis, oxidative tissue injury and thereby the intestinal and hepatorenal side effects of methotrexate treatment. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: beta-glucan; lipid peroxidation; glutathione; Myeloperoxidase activity; TNF-alpha; apoptosis; MACROPHAGE FUNCTION; CYTOKINE RELEASE; RAT MODEL; HEPATOTOXICITY; ACTIVATION; CELLS; DEHYDROGENASES; MECHANISMS; EXPRESSION; TOXICITY